Assessment of sexual and reproductive health knowledge and awareness among single unmarried women living in Lebanon: a cross-sectional study - Maya Hamdanieh; Louna Ftouni; Bara'a Al Jardali; Racha Ftouni; Chaymaa Rawas; Marina Ghotmi; Mohammad Hussein El Zein; Sara Ghazi; Salah Malas (BMC, 2021)
Abstract Background Sexual and reproductive health (SRH), a globally recognized fundamental health concern and a basic human right is poorly addressed and seldom researched in the Arab world. Disregarding this aspect of health creates various obstacles to accessing SRH related services and education. This threatens the health of a female, namely through increasing the probability of unplanned pregnancies and unsafe abortions, augmenting the risk of acquiring sexually transmitted infections, and most importantly, increasing the hazard of maternal and neonatal death. Thus, this study aimed to assess the level of SRH related knowledge and awareness among single unmarried women living in Lebanon. Methods A descriptive cross-sectional study design was conducted using a self-administered questionnaire in both English and Arabic languages. The questionnaire included 9 sections; socio-demographic characteristics section, sexually transmitted infections (STIs) section, premarital tests section, vaccines section, menstruation and its abnormalities section, pregnancy symptoms and identification section, methods of contraception section, vitamins section, and honeymoon events section. The questionnaire was distributed among all Lebanese governorates to 491 single unmarried women living in Lebanon aged between 17 and 55 years. Student t-test and Chi-Square test were used to analyze results. Results It was found that only 8.8% of all the participants had adequate knowledge. The highest level of SRH related knowledge was about pregnancy (88.0%), and the least was about contraception (13.5%). Most of the knowledgeable participants lived in Beirut governorate (13.6%, n = 8) and had reached universities (10.3%, n = 41), but this was not statistically significant (p-value > 0.05). The effect of a prior visit to a gynecologist was statistically non-significant on the overall level of knowledge (p-value = 0.269). Conclusion Due to the inadequate level of knowledge, SRH education campaigns empowered by the Ministry of Public Health in collaboration with primary care physicians and gynecologists, are recommended in both the societal and academic sectors to enhance the awareness level and make SRH knowledge readily available among unmarried women aged between 17 and 55. Knowing the massive role of social media nowadays, the messages they present should contribute to enhancing the level of SRH knowledge and redirect attitudes and behaviors of unmarried females in Lebanon.